2005
DOI: 10.1177/0146167204272311
|View full text |Cite
|
Sign up to set email alerts
|

Implementation Intentions, Perfectionism, and Goal Progress: Perhaps the Road to Hell Is Paved With Good Intentions

Abstract: Two studies explored whether perfectionism moderates the impact of implementation intentions on goal progress. Study 1 used an implementation intention manipulation to examine the effects of these plans in interaction with perfectionism on the progress of New Year's resolutions. Study 2 added a repeated implementation intention condition and monitored affect and monthly goal progress. The results of both studies revealed a significant backfire effect of the implementation intentions on goal progress for partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 30 publications
2
65
0
3
Order By: Relevance
“…To our knowledge only one other study reported that implementation intentions did not produce the desired effect in a defined population: Powers et al (2005) found that socially prescribed perfectionism was associated with worse progress in an implementation intentions condition relative to the control condition. Their data suggested that the formation of implementation intentions for people with pervasive, critical, evaluative concerns appears to evoke a process that can obstruct goal progress.…”
Section: Discussionmentioning
confidence: 82%
“…To our knowledge only one other study reported that implementation intentions did not produce the desired effect in a defined population: Powers et al (2005) found that socially prescribed perfectionism was associated with worse progress in an implementation intentions condition relative to the control condition. Their data suggested that the formation of implementation intentions for people with pervasive, critical, evaluative concerns appears to evoke a process that can obstruct goal progress.…”
Section: Discussionmentioning
confidence: 82%
“…However, those scoring high on socially prescribed perfectionism reported worse goal progress over time when they made implementation intentions compared to when they did not. Relevant for our discussion of health behaviors, one of these studies examined progress toward New Year's resolutions, which included health behavior goals (Powers et al, 2005). Results indicated that formulating implementation intentions elicited negative affect for socially prescribed perfectionists, possibly because focusing on goals aroused negative self-evaluative thoughts about their chances of attaining these goals (Powers et al, 2005).…”
Section: Perfectionism and Self-regulationmentioning
confidence: 99%
“…Self-oriented perfectionism, in comparison, is a more ambivalent form of perfectionism (Enns & Cox, 2002). While selforiented perfectionism too has shown positive correlations with indicators of psychological maladjustment (Hewitt & Flett, 2004), it also has shown significant positive correlations with indicators of good psychological adjustment such as positive affect, goal progress, and academic achievement (e.g., Molnar, Reker, Culp, Sadava, & DeCourville, 2006;Powers, Koestner, & Topciu, 2005;Witcher, Alexander, Onwuegbuzie, Collins, & Witcher, 2007).…”
Section: Perfectionism and The Big Fivementioning
confidence: 99%